REDEFINING SOCIAL MOBILITY IN THE 21ST CENTURY: A CONTEMPORARY CONCEPTUAL FRAMEWORK (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
Classic studies treated social mobility mainly as the movement of individuals up—or down—an income or occupational ladder. Today, scholars and policy institutions frame it more broadly as a multidimensional, life-course process that both reflects and shapes equality of opportunity. This article reconstructs that modern definition, explains why it has widened beyond the “rags-to-riches” trope, and outlines the metrics, drivers, and policy levers that now dominate the field.